Pulsed low-intensity ultrasound increases proliferation and extracelluar matrix production by human dermal fibroblasts in three-dimensional culture. (19th November 2015) - Bohari, Siti PM; Grover, Liam M; Hukins, David WL
This study evaluated the effect of pulsed low-intensity ultrasound on cell proliferation, collagen production and glycosaminoglycan deposition by human dermal fibroblasts encapsulated in alginate. Hoechst 33258 assay for cell number, hydroxyproline assay for collagen content, dimethylmethylene blue assay for glycosaminoglycan content and scanning electron microscopy were performed on the encapsulated cells treated with pulsed low-intensity ultrasound and a control group that remained untreated. Pulsed low-intensity ultrasound showed a significant effect on cell proliferation and collagen deposition but no consistent pattern for glycosaminoglycan content. Alcian blue staining showed that glycosaminoglycans were deposited around the cells in both treated and control groups. These results suggest that pulsed low-intensity ultrasound alone shows a positive effect on cell proliferation and collagen deposition even without growth factor supplements.